The influence of low molecular weight heparin on wound healing in rats - Kuś, Ewa (Menopause Review/Przegląd Menopauzalny, 2005)
The influence of low molecular weight heparine (Clexane) on healing of abdominal wounds in rats was studied. Subcutaneous injections of standard dose of clexane or physiologic saline were given to animals with skin wounds and with prolene mesh inserted into wounds. The collagen concentration was determinated in wound and prolene mesh in control group 14, 21, 28 and 42 days after skin incision and in two groups of rats: treated with clexane for 7 (I group) and 14 (II group) days after skin incision and prolene insertion in 14, 21, 28 and 42 day of wound healing. Clexane administration resulted in signifficant increase of collagen content both in wound and in prolene mesh in total dose – dependent manner.